A proposed energy performance standard for new air-conditioned commercial buildings in Sri Lanka - Jayaweera, Dimuthu Prabath; Surapong Chiraratananon; Bhattacharya, Sribas C.; Supachart c.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1993)
Energy conservation is an important concept for a country. In this regard there is a need to develop an energy efficiency standard for buildings. This study focuses only on new commercial buildings which consume a significant amount of energy. Hourly meteorological data for the year 1992 was used for the calculations. Due to the lack of recorded diffuse radiation data in Sri Lanka,a model have been used to findout the hourly diffuse radiation. Some programs written in Turbo Basic is used for the analysis. The wall thermal mass and absorptivity are taken into consideration . By varying the absorptivity of external surface of the wall,equivalent temperature difference was calculated for different types of wall construction materials. By varying the plane angle of a wall ,solar factor for eight different facades were calculated. To study the impact of shading devices on fenestration, three different types of external shading devices namely Horizontal overhangs, Vertical fins, Eggcrate were used . Shading coefficients were calculated for various sizes of external shading devices. Varying the Window to Wall ratio, possibility of reducing Overall Thermal Transfer Value (OTTV) of different envelope constructions were considered. Three different types of glazing were used for the analysis . Also the effect of adding insulations for opaque walls and the influence on OTTV was analyzed. Normally roofs are well insulated. Therefore in this study not much effort was given towards roofs. Effect of absorptivity on Equivalent Temperature Difference (TDeq> for a horizontal concrete roof and solar factor on the roof was calculated . A model hypothetical building was used to calculate the OTTV for a building in Sri Lanka. Different alternatives were taken for lowering the OTTV of the base case. Also the annual electrical energy consumption for the model building was compared with the standard building. To findout the present OTTV of buildings in Sri Lanka,one existing commercial building was used.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Buildings -- Sri Lanka -- Energy conservation